Digital ecosystems - Tosete-Herranz, Francisco (Anuario ThinkEPI, 2012)
Mobility is the driving force of a radical transformation of society and of our lives, and the emergence of smartphones and tablets has been a turning point. This transformation is mainly articulated around five technological ecosystems, each composed of an operating system, social networks, applications, standards and hardware devices. These ecosystems are the World Wide Web, the social network Facebook, Google, Microsoft and Apple. Only the Web is open; the rest are captives of the companies that are developing them. With the advent of mobility and permanently connected devices such as augmented reality glasses, and the emergence of new digital surfaces in everyday environments such as stores or underground stations, we must try to open the ecosystems to free us from the captive platforms and enable us to build a real life and digital identity independent of that or those with which we work. In this process the Web and W3C standards should once again resume their role as champions.
Keywords: Mobility; Smartphones; Tablets; Digital ecosystem; Open ecosystems; Open technology; World Wide Web; Mozilla; Google; Microsoft; Apple.